Determinant Factors of the Operational Management for Malaysian Umrah Package - Mahmad, Muhamad Amar; Ismail, Nor Hanani; Rofie, Mohamad Khadafi; Ahmad, Shukri (Institute for Political and international Studies (IPIS) of Iran, 2021)
Umrah package operations have recorded a significant increase every year in Malaysia. Muslims need to make various preparations before leaving for umrah including travelling, operational preparations and and the ibadah preparation. Until now, the maintenance of umrah operations is according to USSM. However, this management manual still fails to produce quality management standards in monitoring the entire operation of umrah packages in Malaysia. Some problems still occur such as misuse of operating licenses, taking excessive profits, and handling of unregisteredpackages. Due to this, the study focuses on the management problems of umrah package operations in Malaysia. Using qualitative methods, the findings of the study found that most companies do not have problems while conducting business related to umrah operations. This is because the companies involved have used USSM as themain guide in the operations of umrah. However, two main issues that need to be improved in the USSM, which are related to women's pilgrimage and comprehensive assistance to umrah company operators. Therefore, it is hoped that the proposed improvements will make USSM more effective and can be a model applicable not onlyin Malaysia but also in other countries. There are only two main issues that need to be improved in the USSM, namely related to the women's congregation andcomprehensive assistance to umrah company operators. Therefore, it is hoped that the improvements as proposed will make the USSM more effective and can be appliednot only in Malaysia but also able to be a model of umrah operation to other countries